Modal Minimalis Membawa Berkah di Masa Pandemi Covid-19: Pelatihan Daring Ojek Online - Mohammad Suryadi Syarif; Mia Kamayani; Suciana Wijirahayu (Jurnal Abdimas Adpi Sosial dan Humaniora, 2020)
This public service is inspired by the previous action as one of the volunteers in UHAMKA Covid- 19 action. There were 100 Engineering students’ Online motorbike drivers involved in the project yet the recovery of the pandemi is not over. Therefore further programs in the form of creative industry is provided to develop literacy in enterpreneuship. Practitioners are invited in online workshop to support and inspire the participants who are the drivers and the teachers from vocational high school. Follow-up actions in the form of class actions are carried out online with integrative multimedia in English. The activity was carried out using a method consisting of several steps, namely: student Ojol training participants, training in applying knowledge with character development as a starter, interacting with resource persons, simulating the trainees' understanding of integrative multimedia applications in the creative industry and recording in video form. The results of the implementation of the Creative Industry PKM with integrative multimedia have inspired the participants to develop themselves in the business sector. The English used in the media in the form of videos with online business development materials with minimal capital from resource persons and videos in English from Jack Ma have motivated and improved the ability of student members of the PKM partner online driver community and inspired Abdimas partner teachers to add integrated English content with other subject matter.